2009
DOI: 10.1002/iroh.200911134
|View full text |Cite
|
Sign up to set email alerts
|

Food Resource Partitioning between Two Invasive Gobiid Species (Pisces, Gobiidae) in the Littoral Zone of the River Danube, Hungary

Abstract: At present, the invasive round and bighead gobies are the most abundant benthic fish species in the near shore zone of the Middle Danube. We compared their diet seasonally in natural and artificial habitats and contrasted it with the food supply. The composition of the macroinvertebrate community was determined mainly by seasonal changes, whereas habitat type had smaller effect. Round gobies followed these changes flexibly. They consumed mainly chironomids in the spring, whilst amphipods and molluscs in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
6
38
2
1
Order By: Relevance
“…when available (Table III). The seasonal changes found in the diet of round goby from the Slovak stretch of the Danube followed a similar scenario as those in round goby from Hungary (Borza et al, 2009). In spring, fishes consumed mainly the same food items, i.e.…”
Section: Table IVsupporting
confidence: 58%
See 4 more Smart Citations
“…when available (Table III). The seasonal changes found in the diet of round goby from the Slovak stretch of the Danube followed a similar scenario as those in round goby from Hungary (Borza et al, 2009). In spring, fishes consumed mainly the same food items, i.e.…”
Section: Table IVsupporting
confidence: 58%
“…Similarly, bighead goby exploit the genus of amphipods with the largest body size (Dikerogammarus sp.) almost everywhere in their invaded area (Table II; Borza et al, 2009). Round goby is not reported to be piscivorous in its native range (Pinchuk et al, 2003), nevertheless remnants of fish were found in stomachs of a relatively high number of individuals from the invasive Slovak population (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations